News Verification Suite: Towards System Design to Supplement Reporters’ and Editors’ Judgements - Rubin, Victoria L. (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2018)
This paper offers a conceptual basis and describes elements for a multi-layered system to provide information users (newsreaders) with credible information and improve the work processes of the online news (content) producers. I overview criteria of excellence (what editors consider newsworthy) and how reporters (and traditional newsroom professionals used to) verify information to provide high quality of news. I compare the “traditional model of journalism” to the current journalistic practices of “news sharing a.s.a.p.” and identify certain processes that are currently either missing or could be complemented with automatic verification functions, capitalizing on Natural Language Processing (NLP) and Data-Mining (DM).